2013
DOI: 10.1371/journal.pone.0067731
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Breast Cancer from Fibroadenoma with Dual-Echo Dynamic Contrast-Enhanced MRI

Abstract: Dynamic contrast-enhanced magnetic resonance imaging (DCE MRI) of the breast is a routinely used imaging method which is highly sensitive for detecting breast malignancy. Specificity, though, remains suboptimal. Dynamic susceptibility contrast magnetic resonance imaging (DSC MRI), an alternative dynamic contrast imaging technique, evaluates perfusion-related parameters unique from DCE MRI. Previous work has shown that the combination of DSC MRI with DCE MRI can improve diagnostic specificity, though an additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…These results are in agreement with previous studies performed with other types of solid tumors, including orbital (23), breast (24,25), head and neck (26) and pancreatic tumors (11). A previous study in colorectal cancer is consistent with the present study (27).…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with previous studies performed with other types of solid tumors, including orbital (23), breast (24,25), head and neck (26) and pancreatic tumors (11). A previous study in colorectal cancer is consistent with the present study (27).…”
Section: Discussionsupporting
confidence: 94%
“…High diagnostic accuracy has also been obtained from qualitative assessment of signal loss in T 2 *‐weighted images using dynamic susceptibility contrast (DSC) MRI . Investigators have shown that using DSC MRI in conjunction with DCE MRI may help to distinguish malignant from benign breast lesion . The main limitation using this technique is the need for an additional contrast bolus to measure susceptibility‐induced signal loss with a dynamic T 2 / T 2 *‐weighted sequence.…”
mentioning
confidence: 99%
“…Wang, et al [48] developed a dual-echo GE sequence for simultaneous measurements of T1w DCE MRI and T2*w DSC MRI parameters in the breast that allowed the calculation of semi-quantitative parameters such as blood flow and blood volume. They showed that their approach .…”
Section: Discussionmentioning
confidence: 99%